Equation of state for technetium from X‐ray diffraction and first-principle calculations. (August 2016) - Mast, Daniel S.; Kim, Eunja; Siska, Emily M.; Poineau, Frederic; Czerwinski, Kenneth R.; Lavina, Barbara; Forster, Paul M.
Abstract: The ambient temperature equation of state (EoS) of technetium metal has been measured by X-ray diffraction. The metal was compressed using a diamond anvil cell and using a 4:1 methanol-ethanol pressure transmitting medium. The maximum pressure achieved, as determined from the gold pressureEquation of state for technetium from X-ray diffraction and first-principle calculations scale, was 67 GPa. The compression data shows that the HCP phase of technetium is stable up to 67 GPa. The compression curve of technetium was also calculated using first-principles total-energy calculations. Utilizing a number of fitting strategies to compare the experimental and theoretical data it is determined that the Vinet equation of state with an ambient isothermal bulk modulus of B 0T =288 GPa and a first pressure derivative of B′ =5.9(2) best represent the compression behavior of technetium metal. Highlights: Confirm hexagonal structure of technetium metal up to 67 GPa. Determine first equation of state of technetium by X-ray diffraction. Excellent agreement between X-ray diffraction and DFT equation of state.